The Inuit Tapiriit Kanatami II Case and the Protection of Indigenous Peoples’ Rights: a Missed Opportunity? - VEZZANI, Simone (2016)
On 3 September 2015 the EU Court of Justice dismissed the appeal against the judgment of 25 April 2013, case T-526/10, Inuit Tapiriit Kanatami and Others II, in which the General Court had refused to declare the invalidity of the basic Regulation (EC) No 1007/2009 on trade in seal products pursuant to Article 277 TFUE. Among the issues involved in the case were the legal value under EU law of the UN Declaration on the Rights of Indigenous Peoples and the protection of the appellant indigenous communities’ economic interests by the guarantee accorded to the right to property. Overall, the case reveals a lack of sensitivity of the EU judiciary towards advancing the rights of indigenous peoples and favouring the progressive development of international law in this field.